Restless legs syndrome: Over 50 years of European contribution. (9th July 2022) - Khachatryan, Samson G.; Ferri, Raffaele; Fulda, Stephany; Garcia‐Borreguero, Diego; Manconi, Mauro; Muntean, Maria‐Lucia; Stefani, Ambra
Summary: Restless legs syndrome (RLS) is a sensorimotor neurological disorder characterised by an urge to move the limbs with a circadian pattern (occurring in the evening/at night), more prominent at rest, and relieved with movements. RLS is one of the most prevalent sleep disorders, occurring in 5%–10% of the European population. Thomas Willis first described RLS clinical cases already in the 17th century, and Karl‐Axel Ekbom described the disease as a modern clinical entity in the 20th century. Despite variable severity, RLS can markedly affect sleep (partly through the presence of periodic leg movements) and quality of life, with a relevant socio‐economic impact. Thus, its recognition and treatment are essential. However, screening methods present limitations and should be improved. Moreover, available RLS treatment options albeit providing sustained relief to many patients are limited in number. Additionally, the development of augmentation with dopamine agonists represents a major treatment problem. A better understanding of RLS pathomechanisms can bring to light novel treatment possibilities. With emerging new avenues of research in pharmacology, imaging, genetics, and animal models of RLS, this is an interesting and constantly growing field of research. This review will update the reader on the current state of RLS clinical practice and research, with a special focus on the contribution of European researchers.